Use of progesterone in early detection of open cows in smallholder dairy farms in Nakuru District of Kenya - Indetie, D.; Indetie, A.; Kinyua, J.; Ojango, N.; Perera, O. (TSAP and ILRI, 2006)
Kenya’s smallholder dairy sector produces 85% of the total milk marketed in the country. A major constraint to milk production and number of calves born from the cows is the long calving intervals. Determining non-pregnant cows early by measuring progesterone levels by day 23 after insemination can help reduce calving intervals, thus improving productivity. A sample of 481 cows was inseminated and 10 ml milk samples collected from each cow on day 0, 13 and 23 after insemination to determine progesterone levels using radioimmunoassay and using I125 as the tracer. This was to determine timeliness of artificial insemination (AI), cyclicity and pregnancy by day 24 after AI. Rectal palpation was done 90 days after insemination to confirm hormone predictions for non-pregnancy. Conception rates of 53% were recorded. Mean progesterone levels were 0, 5.3 and 10.1 nm/litre at the three stages of sampling respectively for pregnant cows, while non-pregnant cows recorded 0.59, 2.69, 0.46 nm/litres respectively. Of cows inseminated at the right time, 38% did not conceive, showing a problem of cyclicity or early embryonic loss. Embryonic loss was recorded in 32% of non-pregnant cows. The post-partum period averaged 5 months. Breeds were similar for conception while cows inseminated during April to June had higher conceptions than those of July to September. Prediction accuracy of non-pregnant cows was 96%, thus, open cows can be identified early, reducing the time required to re-breed and hence reduce calving intervals.